(untitled) (American Journal of Islam and Society, 2007)
In this cross-regional comparative study, Stuart Borsch marshals medieval economic data to address why, following the Black Death, “Egypt’s centralized and urban landholding system was unable to adapt to massive depopulation, while England’s localized and rural landholding system had fully recovered by the year 1500” (dust jacket). After making a quick dispatch of antiquated theories and flawed research, he introduces new findings on medieval Egypt’s sharp financial downturn in contrast to England’s economic stabilization and upswing. The author points out that both states were centralized monarchies with similar population levels and agrarian-based economies overseen by “big stick” aristocracies. Egypt had a modicum of arable land along the Nile; England had large areas of pastoral land and far more arable soil (pp. 16-17). In addition, Egypt’s nonhereditary ruling Mamluk elite, imported Caucasian and Central Asian slave children (some of whom actually ruled), became iron-handed absentee landholders: “A vast gulf separated the Mamluk warrior-landholder from the Egyptian peasant. A barracks-trained Turkishor Circassian-speaking Mamluk and a village peasant were probably as ...